Adaptive processes in economic systems - Murphy, Roy E. (New York : Academic Press, 1965)
Mathematics in Science and Engineering, Volume 20, Adaptive Processes in Economic Systems demonstrates the usefulness of communications theory, self-adaptive control theory, and thermodynamic theory to certain economic processes. This book discusses the common properties of adaptive processes, role of the decision maker, and mixed adaptive processes of the first and second kind. The economic environmental processes, concept of entropy time, and stochastic dynamic economic process are also elaborated. This text likewise covers the investment model with full liquidity, adaptive capital allocation process, and concept of an economic state space. Other topics include the stochastic equilibrium in the market and individual adaptive behavior.
Includes bibliographical references
rpm 13/09/2017
Loans
Keywords: Economics